FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI SULAWESI SELATAN - Rusydi, Muhammad (Universitas Muhammadiyah Makassar, 2011)
This study aims to analyze the influence of domestic investment (PMDN), exports, tourism, and the number of companies to the economic growth of South Sulawesi, as well as explain the dominant factors that affect the economic growth of South Sulawesi. The study used secondary data in the form of data on Gross Regional Domestic Product, Investment data, Export, Tourism, and Number of Companies which are entirely obtained from Central Statistics Agency of South Sulawesi Province. The results concluded that based on partial and simultaneous test results, Domestic Investment, Export, Tourism and Number of Companies in Industry sector have a significant effect on economic growth of South Sulawesi.